Developing Tourism Products Through Social Media Training for Rural Communities: Pengembangan Produk Wisata Melalui Pelatihan Media Sosial pada Masyarakat Desa - Fajriaty Muchlis, Nur Farah; Maoudy AB, Andi Fatimah; Wahyuni, Sri (Yayasan Ahmar Cendekia Indonesia, 2024)
The development of Bonto Masunggu Tourism Village in Bone Regency, South Sulawesi, is an effort to enhance community welfare by utilizing the area’s natural and cultural potentials. The village offers natural attractions such as waterfalls and hilly landscapes, along with key products like honey, palm sugar, and mushroom-based goods. This article discusses the village's potential, community empowerment strategies, and the challenges and solutions encountered in tourism village development. Community empowerment through training and digital marketing plays a crucial role in enhancing the value of local products and promoting community engagement. The adoption of technology, infrastructure improvement, and collaboration with the government and private sector are essential to ensure the sustainability of the program. With an integrated approach, Bonto Masunggu Tourism Village is expected to become a sustainable tourism destination that provides economic and social benefits to the local community.